Psychosocial correlates of patient–provider family planning discussions among HIV-infected pregnant women in South Africa - Rodriguez VJ; Cook RR; Weiss SM; Peltzer K; Jones DL (Dove Medical Press, 2017)
Violeta J Rodriguez,1 Ryan R Cook,1 Stephen M Weiss,1 Karl Peltzer,2–4 Deborah L Jones1 1Department of Psychiatry and Behavioral Sciences, University of Miami Miller School of Medicine, Miami, FL, USA; 2HIV/AIDS/STIs and TB (HAST) Research Programme, Human Sciences Research Council, Pretoria, South Africa; 3ASEAN Institute for Health Development, Mahidol University, Salaya, Thailand; 4Department of Psychology, University of Limpopo, Turfloop, South Africa Abstract: Patient–provider family planning discussions and preconception counseling can reduce maternal and neonatal risks by increasing adherence to provider recommendations and antiretroviral medication. However, HIV-infected women may not discuss reproductive intentions with providers due to anticipation of negative reactions and stigma. This study aimed to identify correlates of patient–provider family planning discussions among HIV-infected women in rural South Africa, an area with high rates of antenatal HIV and suboptimal rates of prevention of mother-to-child transmission (PMTCT) of HIV. Participants were N=673 pregnant HIV-infected women who completed measures of family planning discussions and knowledge, depression, stigma, intimate partner violence, and male involvement. Participants were, on average, 28 ± 6 years old, and half of them had completed at least 10–11 years of education. Most women were unemployed and had a monthly income of less than ~US$76. Fewer than half of the women reported having family planning discussions with providers. Correlates of patient–provider family planning discussions included younger age, discussions about PMTCT of HIV, male involvement, and decreased stigma (p < 0.05). Depression was indirectly associated with patient–provider family planning discussions through male involvement (b = −0.010, bias-corrected 95% confidence interval [bCI] [−0.019, −0.005]). That is, depression decreased male involvement, and in turn, male involvement increased patient–provider family planning discussions. Therefore, by decreasing male involvement, depression indirectly decreased family planning discussions. Study findings point to the importance of family planning strategies that address depression and facilitate male involvement to enhance communication between patients and providers and optimize maternal and neonatal health outcomes. This study underscores the need for longitudinal assessment of men’s impact on family planning discussions both pre- and postpartum. Increasing support for provision of mental health services during pregnancy is merited to ensure the health of pregnant women living with HIV and their infants. Keywords: family planning, women, HIV, South Africa, pregnancy, contraception